Banda Aceh Metamorphosis: Analyzing The Impact of Urban Sprawl in Meuraxa District - Rahmah, Siti; Fadhly, Noer; Irwansyah, Mirza (Riviera Publishing, 2023)
The rapid development of Banda Aceh City has led to a surge in population growth, causing unstructured development in suburban areas, particularly in Meuraxa District, where the land use has undergone a significant transformation. This research aims to analyze the impact of urban sprawl on the form of the city of Banda Aceh in terms of the physical condition of Meuraxa District. Utilizing a quantitative approach with geographic analysis, the study employs remote sensing and GIS (Geographic Information System) applications, specifically ArcGIS SHP map data. The analysis covers the period from 2010 to 2020, revealing a noteworthy increase in housing land use in Meuraxa District. The findings indicate that Meuraxa District has experienced urban sprawl, evidenced by the reduction in undeveloped land, there was an increase in land use for housing, improved accessibility, and increased availability of facilities. The GIS data-based urban sprawl development model categorizes Meuraxa District as an